NILAI GEOSTRATEGIS SELAT GIBRALTAR BAGI SPANYOL PASCA REFERENDUM KE-II TAHUN 2012-2015 - Madeli, Inggrid Putri; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research analyzes geostrategic value of Gibraltar for Spain. This research want to know why did Spain keep on preassuring Gibraltar. The small region on point of Europe has much values such as economic, geopolitic and tourism. Those values made England and Spain had conflict. This is the reason why the writer interested in this research. This dispute started when Spain transfered sovereignty of Gibraltar to England in SpanishSuccession War. Spain dispute Gibraltar from England because it had much potentials and very strategic. As the consequence, Gibraltar made twice referendum; on 1967 and 2002. The result of the referendum was Gibraltar people continued to live under England and rejected be apart of Spain. In another side, the geostrategic value of Gibraltar in politic, security, and economic.This is qualitative research which used descriptive explanative methods. This paper used the realist perspective and policy theory proposed by K.J Holsti and Rosneau. Writer using level analysis of state, because this conflict involve two state. that is method to explain the problem in aparticular and method library research, such as books, journals, magazine, media electronic, and the other source.The result of this research explained that geostrategic value of Gibraltar for Spain is in economic, geopolitic and security. If Spain Succeeds to have sovereignty of Gibraltarthen Spain will have more power in international politic especially in continental regions of Europe.in security Gibraltar has much strategic value because Gibraltar have â The Rockâ that could be used as military base for Spain. In economic Spain will have benefit from various sectors such as tourism ,financial services and others.Key Words: Geostrategic, Geopolitic, Referendum, Utrecht treaty.